Associação entre métodos de adaptabilidade e de estabilidade em feijão - Maziero, Sandra Maria (2011)
The study of adaptability and yield stability allows to identify cultivars adapted to specific conditions and wide, stable and with high grain yield, and can be realized as the different methodologies employed. Thus, the aim of this study was to investigate the association between adaptability and stability methods for grain yield in common bean cultivars and identify the most promising for cultivation in State of Rio Grande do Sul. For this, were used the Eberhart and Russell (1966), the Cruz et al. (1989), the additive main effects and multiplicative interaction analysis (AMMI), the Lin and Binns (1988) modified and the Annicchiarico (1992) methods, and, in the first three methods, the average grain yield was considered as a parameter of stability and adaptability. The competition trials of common bean cultivars were conducted in randomized block experimental design with three replications, during the growing seasons from 2000 to 2008, in ten different places of Rio Grande do Sul State, in different crop cultivation and harvesting period, totaling 24 experiments. We evaluated 12 common bean cultivars of different commercial groups (black, carioca and cranberry): Diamante Negro, Guapo Brilhante, Guateian 6662, IAPAR 44, Macanudo, Macotaço, Minuano, Tio Tibagi, TPS Nobre, Carioca, Pérola and Iraí. Significative cultivars x environments interaction were observed for grain yield. The TPS Nobre cultivar was the one closest to praised as ideal behavior, except for the AMMI analysis. While the Iraí cultivar was unstable and had low grain yield in Rio Grande do Sul State. Significative correlation was observed among Eberhart and Russell (1966), Cruz et al. (1989), AMMI, Lin and Binns (1988) modified and Annicchiarico (1992) methods, demonstrating that they are associated. Lin and Binns (1988) modified (rs = 0.95) and Annicchiarico (1992) (rs = 0.97) methodologies were highly correlated with the average grain yield and allowed the identification of stable and adapted cultivars among the most productive. Thus, in analysis of adaptability and stability for common bean crop, when the average grain yield is considered as a parameter of adaptability and stability, not recommended to use together of Eberhart and Russell (1966), Cruz et al. (1989), AMMI, Lin and Binns (1988) modified and Annicchiarico (1992) methods. Choosing the most appropriate method is at the discretion of the researcher.